Designing with Light - Gillette J.Michael (McGraw -Hill, 2007)
This comprehensive survey of the practical and aesthetic aspects of basic stage lighting design treats its subject as an art closely integrated with that of the director, actor, and playwright, and as a craft that provides practical solutions for the manipulation of stage space. An eight-page color section provides a discussion of the practical applications of color theory as well as an analysis of the color choices for the lighting design of an actual production. Numerous illustrations of technical tools, equipment, and exemplary play designs visualize designing with light for students